Islamic Republic of Afghanistan : 2007 Article IV Consultation and Third Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, and Request for Waiver of Performance Criterion; Staff Report; Staff Statement; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Islamic Republic of Afghanistan. (IMF Staff Country Reports; Country Report ;, 2008)
Afghanistan has made substantial progress toward macroeconomic stability, but structural reforms need to be accelerated. The uncertainty affecting the fiscal outlook warrants a prudent expenditure policy. Monetary policy has been instrumental in reducing inflation and safeguarding external stability, but it needs to be strengthened. The government should resist pressures for expanding its role in the economy and focus on fostering competition and improving economic governance. The current exchange rate level appears in line with fundamentals. The government should increase its efforts to improve Afghanistan's statistical database.